Learner profile stability and change over time: the impact of the explicit strategy instruction program "learning light". Issue 1 (10th February 2020) - Rogiers, Amelie; Merchie, Emmelien; Keer, Hilde Van
Abstract: This study examined the stability and change in secondary school students' learner profiles after receiving an explicit strategy instruction (ESI) to foster their text-learning strategy use. A randomized quasi-experimental repeated measures design was set up with one experimental condition – receiving an eight-lesson-teacher delivered instructional treatment – and one control condition. Four learner profiles (i.e., integrated strategy users, information organizers, mental learners, and limited strategy users) were corroborated at three measurement occasions in a sample of 444 students. Cluster movement analysis identified positive changes in students' learner profiles over time. Both short- and long-term results were promising.